Firestorm : how wildfire will shape our future - Struzik, Edward, 1954- (Washington, DC : Island Press, 2017)
'In the spring of 2016, the world watched as wildfire ravaged the Canadian town of Fort McMurray. Firefighters named the fire'the Beast' because it behaved in seemingly sinister and often unpredictable ways. Many of them hoped that they would never see anything like it again. Yet it's not a stretch to suggest that megafires like the Beast have become the new normal. A glance at international headlines shows a remarkable increase in higher temperatures, stronger winds, and drier lands--a trifecta for igniting wildfires like we have rarely seen before. Fires are burning bigger, hotter, faster, and more often. In Firestorm, journalist Edward Struzik confronts this new reality, offering a deftly woven tale of science, economics, politics, and human determination. To understand how we might yet flourish in the coming age of megafires, Struzik visits scorched earth from Alaska to Maine, and introduces the scientists, firefighters, and resource managers making the case for a radically different approach to managing wildfire in the twenty-first century. We must begin by acknowledging that fire is unavoidable, and be much more prepared to cope when we cannot completely control the flames. Living with fire also means, Struzik reveals, that we must better understand how the surprising, far-reaching impacts of these massive fires will linger long after the smoke eventually clears'--Jacket flap.
The beast awakens -- Inside the mind of a wildfire -- A history of fire suppression -- Visions of the Pyrocene -- Water on fire -- The big smoke -- Drought, disease, insects, and wildfire -- Fire on ice -- Agent of change -- Resilience and recovery.
Includes bibliographical references (pages 249-257).
Keywords: Wildfires -- North America; Wildfires -- Environmental aspects; Wildfires -- Prevention and control -- History; Wildfires -- North America -- Prevention and control; Fire ecology -- North America; Forest policy -- United States; Forest policy -- Canada; History